MicroRNA delivery through nanoparticles - Lee, Sharon Wei Ling; Paoletti, Camilla; Campisi, Marco; Osaki, Tatsuya; Adriani, Giulia; Kamm, Roger D.; Mattu, Clara; Chiono, Valeria (Journal of controlled release, 2019)
MicroRNAs (miRNAs) are attracting a growing interest in the scientific community due to their central role in the etiology of major diseases. On the other hand, nanoparticle carriers offer unprecedented opportunities for cell specific controlled delivery of miRNAs for therapeutic purposes. This review critically discusses the use of nanoparticles for the delivery of miRNA-based therapeutics in the treatment of cancer and neurodegenerative disorders and for tissue regeneration. A fresh perspective is presented on the design and characterization of nanocarriers to accelerate translation from basic research to clinical application of miRNA-nanoparticles. Main challenges in the engineering of miRNA-loaded nanoparticles are discussed, and key application examples are highlighted to underline their therapeutic potential for effective and personalized medicine.